VASCULAR COMPLICATIONS IN LONG COVID ARE VERY RARE - Končar, Igor (Medicinski podmladak, 2023)
Depending on the methodology thrombotic events during the acute COVID-19 infection were noted from 20-85%. Following the acute phase of the disease, it was noted that a subgroup of patients had various non-specific, prevailing symptoms for weeks, or even months and such a condition was accepted as a long COVID. Having in mind mechanisms of vascular complications in acute COVID infection and pathogenesis of long COVID, one would expect similar presentation and consequences of long COVID on human vasculature. We conducted a wide search of the literature on the topic and after screening of titles and abstracts papers with potential inclusion of the data regarding long COVID and vascular symptoms or complications that occurred during the time span of more than then 4 weeks after COVID infection. Research dealing with long COVID are mostly focused on symptoms and laboratory findings due to the nature of this condition. Data regarding vascular complications in these studies are either missing or the incidence of vascular complications was very low. Very few manifestations were related to cardiovascular system and D-dimer was assessed in only two studies showing increased values from very lot to almost in 30% of patients after COVID infection. Finally, in comparison of vascular complications with other viral infections in Sweden on patients undergoing diagnostic tests for venous thromboembolism increased risk for VTE in COVID-positive patients was proved. In the group of patients with chronic cardiovascular disease, the risk of arterial and venous thrombotic events after COVID infection is substantially higher. In comparison with seasonal influenza burden with coagulation disorders, pulmonary embolism, acute phlebitis, thrombophlebitis or thromboembolism and arterial embolism were higher and cumulative incidence was reported from 0.6-5.5% while hazard ration was from 2-18.    Based on the published literature, vascular complications in the long COVID are very rare. Comparing to a very high rate of thrombotic events in the acute COVID infection and their correlation with severity of clinical presentation of COVID infection, the role and presence of vascular complications in long COVID is without any significance. Future studies focusing on the pathophysiology of long COVID could probably reveal potential mechanisms and explanations for such a difference.
Keywords: vascular complications; thrombosis; ischemia; pulmory embolism; vein thrombosis; arterial thrombosis; emoblisation; long COVID